GLP-1 receptor signalling promotes β-cell glucose metabolism via mTOR-dependent HIF-1α activation - Carlessi, Rodrigo; Chen, Y.; Rowlands, J.; Cruzat, Vinicius; Keane, Kevin; Egan, L.; Mamotte, Cyril; Stokes, R.; Gunton, J.; Bittencourt, P.; Newsholme, Philip (Nature Publishing Group, 2017)
Glucagon-like peptide-1 (GLP-1) promotes insulin secretion from pancreatic ß-cells in a glucose dependent manner. Several pathways mediate this action by rapid, kinase phosphorylation-dependent, but gene expression-independent mechanisms. Since GLP-1-induced insulin secretion requires glucose metabolism, we aimed to address the hypothesis that GLP-1 receptor (GLP-1R) signalling can modulate glucose uptake and utilization in ß-cells. We have assessed various metabolic parameters after short and long exposure of clonal BRIN-BD11 ß-cells and rodent islets to the GLP-1R agonist Exendin-4 (50 nM). Here we report for the first time that prolonged stimulation of the GLP-1R for 18 hours promotes metabolic reprogramming of ß-cells. This is evidenced by up-regulation of glycolytic enzyme expression, increased rates of glucose uptake and consumption, as well as augmented ATP content, insulin secretion and glycolytic flux after removal of Exendin-4. In our model, depletion of Hypoxia-Inducible Factor 1 alpha (HIF-1a) impaired the effects of Exendin-4 on glucose metabolism, while pharmacological inhibition of Phosphoinositide 3-kinase (PI3K) or mTOR completely abolished such effects. Considering the central role of glucose catabolism for stimulus-secretion coupling in ß-cells, our findings suggest that chronic GLP-1 actions on insulin secretion include elevated ß-cell glucose metabolism. Moreover, our data reveal novel aspects of GLP-1 stimulated insulin secretion involving de novo gene expression.